Quality Assurance System in Improving the Quality of Education in Schools - Mohzana Mohzana; Arifin, Muhammad; Iswahyu Pranawukir; Ardhana Januar Mahardhani; Ahmad Hariyadi (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
This research aims to describe a quality assurance system in improving the quality of education. The method used is a field description. The approach is a qualitative approach. The data collection methods used are observation, interviews and documentation. The stages in data analysis techniques are, collecting data, reducing data, presenting data and drawing up research. The results of this research are as follows, 1. The quality assurance system in improving the quality of education in schools has not been running well, one of which is the participation of education stakeholders to support quality development, and lack of funding allocation, 2. There are several factors inhibiting the quality assurance system in improving The quality of education in schools is as follows, the self-evaluation tools used in self-evaluation activities in schools have not been used optimally and also all teachers and parents have not been able to optimize school self-evaluations. 3. Efforts made to overcome factors inhibiting the quality assurance system in improving the quality of education in schools are improving quality fulfillment, increasing quality priorities that have not been achieved, improving quality findings and improving aspects of quality improvement.